Role of Heparin in Arterial Line Flushing Solution on Platelet Count and Indwelling Arterial Catheter Patency after Cardiac Valvular Surgery - Hossain, Md Anwar; Alam, Mohammad Jahangir; Begum, Razia; Sarker, Rampada; Ahmed, Imran; Reza, Md Mohashin (Bangladesh Heart Journal, 2018)
Background: Heparin can cause thrombocytopenia but what is it’s effect on platelet when used in solution for flushing indwelling arterial catheter is not clear. This study was designed to find out any effect of heparin on platelet count and to see the efficacy of normal solution as flushing solution. Method:This was a prospective randomized comparative clinical trial in the Department of Cardiovascular Surgery of National Institute of Cardiovascular Diseases Hospital, Sher - e - Banglanagar, Dhaka,Bangladesh during the period from july 2016 to june 2017. Total sixty patients who underwent single valve replacement surgery were divided into two groups and were evaluated for heparin effect and compared for arterial catheter patency rate. Results: Platelet count on third postoperative day is 226517+- 60185/ml and 245957+-52826/ml in heparinized flush solution and normal saline flush solution group respectively. The difference of mean is not significant with p value 0.188. Arterial catheter patency rate was 50.0% in heparinized flush solution group and 43.3% in normal saline flush solution group on third postoperative day which signifies no difference between the groups with p value 0.607. Conclusion: The use of heparin in normal saline in continuous flushing devices for an arterial catheter does not significantly reduce platelet counts in cardiac valve surgery patients in comparison to normal saline. It seems that there is no difference in the use of heparinized and normal saline solutions to maintain indwelling arterial catheter patent. Bangladesh Heart Journal 2018; 33(1) : 61-66